The Stars of Freedom - Gloria D. Rall (Symphony in the Flint Hills, 2019)
Introduction: In pre-Civil War America, escaping slaves learned elementary astronomy, journeyed toward the Big Dipper, and made their way to freedom. (Reproduced from: Sky & Telescope, Gloria D. Rall, published by American Astronomical Sociey, Feb. 1995.)